An Analysis of Chinese Transport Infrastructure Loans and Investment in ICT in Nigeria - Innocent .A. Ocholi; Nnamdi .S. Okonkwo (International Studies Journal)
Modern digital and physical infrastructures are critical to national security and socio-economic development. It is within this context that Nigeria obtained huge loans from China-Exim Bank and attracted significant FDI from private Chinese companies to modernize her broken down physical infrastructure and obsolete ICT ecosystem. Since the thrust of the paper is an enquiry after the fact, the Ex-Post-Facto research design was adopted for data collection while the theory of absolute and relative gains was applied as a theoretical framework. The paper discovered that the exact terms and conditions embedded in the performance and implementation frameworks were not disclosed. This raised questions of transparency in the loan packaging process. The paper also discovered that in the other African and Asian countries where China had given out such infrastructure loans in the past, a high level of hidden cost was attached. The undisclosed hidden cost attached to Chinese infrastructure loans and the concessions given to private Chinese companies to do business at will in Nigeria has created a high level of balance of trade deficit in favour of China. The possibility of debt insolvency has serious implications for national security and socio-economic development the future. It is against this backdrop that the paper concludes that the Chinese infrastructure loans and ICT investments are potential debt traps foisted on Nigeria with grave negative implications for the future. Recommendations were suggested as a way forward.